Comparison of microbiological assay and HPLC-UV for determination of fluconazole in capsules - Kelly Marques Queiroz; Maria-Luiza Martins Silva; Nathália Duque Prado; Paulo Marcelo Andrade Lima; Rosiane Dias Lopes Diniz; Isabela Costa César; Gerson Antônio Pianetti; Daniel Assis Santos (Universidade de São Paulo, 2009)
The development of a specific agar diffusion bioassay for the quantitative determination of fluconazole formulated in capsules was carried out using a strain of Candida albicans ATCC 18804 as the test organism. A prospective validation of the method showed adequate linearity (r²=0.9995), precision (R.S.D. = 4.0% for intra-day and 4.5% for inter-day precision) and accuracy (mean recovery = 102.9%). High performance liquid chromatography was chosen as a comparison method for the fluconazole determination. The contents of fluconazole determined by both methods, for four capsule samples, showed a strong correlation, confirmed by Pearson's correlation coefficient value (r = 0.9884). The bioassay is a suitable method for both research and pharmaceutical industry laboratories. Este trabalho visou ao desenvolvimento e validação de um método microbiológico por difusão em ágar para quantificação de fluconazol em cápsulas utilizando o isolado Candida albicans ATCC 18804 como reagente biológico. O método foi validado e foi verificada linearidade (r²=0,9995), precisão (D.P.R. = 4.0% para precisão intra-dia e 4,5% para precisão inter-dia) e exatidão (recuperação média = 102,9%). Concomitantemente, foi realizado o doseamento de fluconazol nas cápsulas por meio de cromatografia líquida de alta eficiência. Os teores encontrados por ambos os métodos demonstraram alta correlação, confirmada pelo Coeficiente de Correlação de Pearson (r = 0,9884). O ensaio microbiológico desenvolvido pode ser considerado ferramenta valiosa tanto para a pesquisa científica quanto para a rotina da indústria farmacêutica.